망막전막 환자의 유리체절제술 후 형태적 및 기능적 회복의 예후인자 분석 - 하계림(Gye Lim Ha); 정소연(Soyeon Jung); 진희승(Hee Seung Chin); 이동현(Dong Hyun Lee) (Daihan angwa haghoi jabji, 2025)
목적: 망막전막 환자에서 유리체절제술 후 기능적 및 형태적 회복에 영향을 미치는 예후인자를 분석하고자 한다. 대상과 방법: 2009년 1월부터 2021년 8월까지 본원에서 망막전막으로 유리체절제술을 받은 환자들을 대상으로 후향적 연구를 진행하였다. 수술 후 6개월째 시점의 최대교정시력 및 중심황반두께를 분석하여 기능적 및 형태적 예후를 평가하였으며, 로지스틱 회귀분석을 통해 예후인자를 분석하였다. 결과: 총 77명의 환자가 포함되었으며, 35.1%가 남성이었다. 38명의 환자는 유리체절제술과 백내장 제거술을 동시에 받았다. 로지스틱 회귀분석 결과 수술 전 최대교정시력이 좋을수록 좋은 시력 예후를 나타내었다(p=0.002). 백내장수술을 함께 시행한 군(38안, 49.4%)에서는 단변량 분석 시 수술 전 안축장이 길수록 시력 예후가 좋았으나(p=0.043), 다변량 분석에서는 유의한 차이를 나타내지않았다(p=0.064). 아울러, 수술 당시 나이가 어릴수록, 수술 전 중심황반두께가 얇을수록 수술 후 좋은 형태적 예후를 나타내었다(p=0.034, 0.001). 결론: 망막전막 환자에서 수술 전 최대교정시력, 수술 당시 나이, 수술 전 중심황반두께 및 안축장이 유리체절제술 후 기능적 혹은형태적 예후와 관련된 인자이며, 수술 전 환자의 치료 계획 및 예후 예측에 도움이 될 수 있을 것으로 기대한다. Purpose: To analyze prognostic factors for morphological and functional recovery after vitrectomy in patients with idiopathic epiretinal membrane (ERM). Methods: We conducted a retrospective analysis of patients with ERM who underwent vitrectomy. Postoperative outcomes were evaluated in terms of functional and morphological changes, assessing best-corrected visual acuity (BCVA) and central macular thickness (CMT) after 6 months. Logistic regression was used to identify factors influencing postoperative outcomes. Results: This study included 77 patients (35.1% men). Thirty-eight patients underwent combined vitrectomy and cataract surgery. Logistic regression revealed that better preoperative BCVA was associated with improved postoperative BCVA (p = 0.002). Among the 38 eyes that underwent combined surgery, longer preoperative axial length was linked to better visual outcomes in univariate analysis (p = 0.043), although the association was not statistically significant in multivariate analysis (p = 0.064). Younger age and thinner preoperative CMT were associated with better morphological outcomes (p = 0.034 and p = 0.001, respectively). Conclusions: Preoperative BCVA, age, preoperative CMT, and axial length are predictive factors for functional and morphological outcomes after vitrectomy in patients with ERM. These findings may facilitate treatment planning and prognosis prediction before surgery. KCI Citation Count: 0